1991
DOI: 10.1177/026309239101000402
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Broadband, Tonal and Masked Ventilation Noise on Performance, Wakefulness and Annoyance

Abstract: A laboratory study was designed in order to investigate the effects of ventilation noise on performance, fatigue and annoyance. The study was also designed in order to compare the effects of broadband noise 40 dB(A), tonal noise, 40 dB(A), and tonal noise masked by means of low frequency pink noise, 41 dB(A). The study of performance was based on a figure identification test. The annoyance and fatigue were tested by means of rating scales. The analyses of fatigue also included EEG-recordings. The acceptability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 1 publication
1
14
1
1
Order By: Relevance
“…In the field of occupational medicine, several studies claim that low-frequency noise is an agent that interferes with the performance of work tasks [25,[27][28][29] and that low-frequency noise can affect mental and physical health.…”
Section: Low-frequency Noise and Human Well-beingmentioning
confidence: 99%
“…In the field of occupational medicine, several studies claim that low-frequency noise is an agent that interferes with the performance of work tasks [25,[27][28][29] and that low-frequency noise can affect mental and physical health.…”
Section: Low-frequency Noise and Human Well-beingmentioning
confidence: 99%
“…Landström et al found no significant difference in performance on a figure identification test when comparing a broadband ventilation noise to a second broadband ventilation noise with a tone added at 100 Hz ͑both at L Aeq = 40 dBA͒. 30 However, when comparing the tonal noise to the same noise with a masking pink noise ͑41 dBA͒ added in the frequency range of 50-200 Hz, they found a tendency toward better performance, higher wakefulness, higher annoyance, and lower tolerated levels under the pink noise added exposure. 30 The fact that differences were seen when comparing the tonal noise to the masked noise but not when comparing the tonal noise to the broadband noise indicates that the types of noise conditions used play a strong role.…”
Section: Noise Condition Vesus Task Performancementioning
confidence: 99%
“…Much work has been conducted on loudness and annoyance of tones in noise, [27][28][29][30][31][32] but little has been done to correlate these with commonly used indoor noise criteria systems. Modern HVAC systems are replete with examples of pure tones.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicate that the presence of tones can impact perception or performance (Landström et al 1991(Landström et al , 1994Holmberg et al 1993;Ryherd and Wang 2010), but none of the investigations could provide guidelines for what the threshold of annoyance for tones in noise should be across a wide range of tonal frequencies. Further work is required to link the degree of tonalness in noise to human annoyance thresholds.…”
Section: Previous Researchmentioning
confidence: 99%